The Influence of Brazilian Culture on Organizational Structure, Employee Motivation and Recruitment and Selection Practices, While Considering German Practices, is Significant - Shalwani, Anoosha (Advances in Social Sciences Research Journal, 2024)
Organizational behavior (OB) focuses on studying the behavior of people within organizations. It aims to understand, predict, and influence human behavior an structure to enhance organizational performance. Globalization refers operating and competing in the global economy while upholding social responsibilities and business ethics. There is a prediction by French that the global shortage of workers may decrease in the future. Additionally, adopting cross-cultural approach in OB helps in recognizing variations in workplace attitudes and behavior among individuals and groups (Christy, 11th edition, 2016). Geert Hofstede identified four cultural dimensions: power distance, uncertainty avoidance, individualism, and masculinity, Additionally, Fon Trompenaars, Charles Hampden- Turner identified seven areas in which cultural differences affect aspects of organizational behavior. These areas include relationships and roles, individual oriented societies, the display of emotions in public, the significance of building relationships in diffuse cultures, and the value of achievements within societies, the shift from collectivism towards individualism in Brazil validates Hofstede’s assumption about cultural change due to global economic growth. (Podrug, et al., n.d.).